Altered Cortical Activation in Adolescents With Acute Migraine: A Magnetoencephalography Study - Xiang, Jing (2013)
To quantitatively assess cortical dysfunction in pediatric migraine, 31 adolescents with acute migraine and age- and gender-matched controls were studied using a magnetoencephalography (MEG) system at a sampling rate of 6,000 Hz. Neuromagnetic brain activation was elicited by a finger-tapping task. The spectral and spatial signatures of magnetoencephalography data in 5 to 2,884 Hz were analyzed using Morlet wavelet and beamformers. Compared with controls, 31 migraine subjects during their headache attack phases (ictal) showed significantly prolonged latencies of neuromagnetic activation in 5 to 30 Hz, increased spectral power in 100 to 200 Hz, and a higher likelihood of neuromagnetic activation in the supplementary motor area, the occipital and ipsilateral sensorimotor cortices, in 2,200 to 2,800 Hz. Of the 31 migraine subjects, 16 migraine subjects during their headache-free phases (interictal) showed that there were no significant differences between interictal and control MEG data except that interictal spectral power in 100 to 200 Hz was significantly decreased. The results demonstrated that migraine subjects had significantly aberrant ictal brain activation, which can normalize interictally. The spread of abnormal ictal brain activation in both low- and high-frequency ranges triggered by movements may play a key role in the cascade of migraine attacks. PERSPECTIVE: This is the first study focusing on the spectral and spatial signatures of cortical dysfunction in adolescents with migraine using MEG signals in a frequency range of 5 to 2,884 Hz. This analyzing aberrant brain activation may be important for developing new therapeutic interventions for migraine in the future.